2014
DOI: 10.1142/s1758825114500112
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Wave Propagation and Vibration of Circular Nanostructures Based on Nonlocal Elasticity Theory

Abstract: The presence of size effects represented by a small nanoscale on torsional wave propagation properties of circular nanostructure, such as nanoshafts, nanorods and nanotubes, is investigated. Based on the nonlocal elasticity theory, the dynamic equation of motion for the structure is formulated. By using the derived equation, simple analytical solutions for the relation between wavenumber and frequency via the differential nonlocal constitutive relation and the numerical solutions for a discrete nonlocal model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…However, the expressions for the classical stress and the stress gradient resultants given in non-dimensional form in Eqs. (36) and (37) are not dened whenμ 0 =l s . In this case, using Eqs.…”
Section: Equations Of Motion Of Size-dependent Rodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expressions for the classical stress and the stress gradient resultants given in non-dimensional form in Eqs. (36) and (37) are not dened whenμ 0 =l s . In this case, using Eqs.…”
Section: Equations Of Motion Of Size-dependent Rodsmentioning
confidence: 99%
“…Arda and Aydogdu [35] investigated analytically the static and free vibration response of a carbon nanotube (CNT) embedded in an elastic medium. Islam et al [36] obtained analytical solutions for the wave propagation problem of an innitely long torsional CNT rod. Li [37] developed two dierent nonlocal elasticity models to study the torsional vibration response of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al (2012a) pointed that in a homogeneous layer over a heterogeneous half-space torsional waves do exist. The commendable works by Islam et al (2014), Chattopadhyay et al (2012cChattopadhyay et al ( , 2013b, Kalyani et al (2008), Pal and Mandal (2014) in the study of seismic waves may be cited.…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al studied the size effects on the torsional wave propagation properties of circular nanostructure. The effect of nanoscale on natural frequency for finite nanotube/nanorod is investigated based on the integral nonlocal constitutive relation and it was concluded that the torsional wave dispersion characteristics for a circular nanostructure was significantly different from the classical model [Islam et al, 2014].…”
Section: Introductionmentioning
confidence: 99%